Evaluation of antimicrobial edible coatings from a whey protein isolate base to improve the shelf life of cheese - O. L. Ramos (2012)
The objective of this work was to evaluate the effectiveness of antimicrobial edible coatings to wrap cheeses, throughout 60 d of storage, as an alternative to commercial nonedible coatings. Coatings were prepared using whey protein isolate, glycerol, guar gum, sunflower oil, and Tween 20 as a base matrix, together with several combinations of antimicrobial compounds-natamycin and lactic acid, natamycin and chitooligosaccharides (COS), and natamycin, lactic acid, and COS. Application of coating on cheese decreased water loss (~10%, wt/wt), hardness, and color change; however, salt and fat contents were not significantly affected. Moreover, the antimicrobial edible coatings did not permit growth of pathogenic or contaminant microorganisms, while allowing regular growth of lactic acid bacteria throughout storage. Commercial nonedible coatings inhibited only yeasts and molds. The antimicrobial edible coating containing natamycin and lactic acid was the best in sensory terms. Because these antimicrobial coatings are manufactured from food-grade materials, they can be consumed as an integral part of cheese, which represents a competitive advantage over nonedible coatings.